Understanding institutional changes in irrigation management: a comparative case study of two communities in the Venezuelan Andes. Issue 8 (17th November 2022) - Leroy, David; García, Sara Barrasa; Porto Tapiquén, Efraín
ABSTRACT: This paper explores institutional changes in two water users' associations (WUAs) in the Venezuelan Andes. The methodology is based on ethnographic work. The results show that both WUAs have modified the rule systems in irrigation management to respond to economic, institutional and environmental changes. They have implemented a better organization of water sharing, adopted more efficient irrigation technologies, restored infrastructure and preserved high-altitude wetlands. The comparative approach adopted allowed us to show not only the similar factors that promoted institutional change, such as social capital, but also the differences related to the characteristics of the resource.